1997
DOI: 10.1136/gut.40.6.801
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathy associated T cell lymphoma presenting as an isolated CNS lymphoma three years after diagnosis of coeliac disease: T cell receptor polymerase chain reaction studies failed to show the original enteropathy to be a clonal disorder.

Abstract: A case of enteropathy associated T cell lymphoma is reported in a 45 year old woman, presenting with isolated disease in the CNS, three years after diagnosis of coeliac disease. Initial staging showed no evidence of gastrointestinal tract lymphoma. A presumptive diagnosis of T cell primary cerebral lymphoma was made and the patient was treated with combination chemotherapy and craniospinal radiotherapy. The patient relapsed, seven months after treatment, with small bowel lymphoma. The inmunophenotype and T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…We added intermediate-dose MTX to the protocol as prophylaxis against previously described relapse/progression of disease in the central nervous system. 24,25 Treatment starts with 1 cycle of CHOP to establish initial disease control; to minimize the risk of side effects such as perforation, anastomotic breakdown, or wound dehiscence (in the postsurgery patient); and to allow a limited recovery period before the more intensive part of the regimen begins.…”
Section: Discussionmentioning
confidence: 99%
“…We added intermediate-dose MTX to the protocol as prophylaxis against previously described relapse/progression of disease in the central nervous system. 24,25 Treatment starts with 1 cycle of CHOP to establish initial disease control; to minimize the risk of side effects such as perforation, anastomotic breakdown, or wound dehiscence (in the postsurgery patient); and to allow a limited recovery period before the more intensive part of the regimen begins.…”
Section: Discussionmentioning
confidence: 99%
“…The SNLG reported 6% of patients with bone marrow infiltration [25••]. One particular extranodal site of involvement in EATL worth special mention is the central nervous system, which is rarely involved at presentation [28] but may be the only site of relapse, particularly late relapse [29]. Treatment outcomes in this situation are very poor.…”
Section: Epidemiology and Clinical Featuresmentioning
confidence: 99%
“…[378] Recent research findings based on gene analysis studies have suggested that there may be two distinct subtypes of EATL. Type I accounts for 80 to 90 percent of cases, and is strongly associated with celiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…The neoplastic lymphocytes stain positively for CD45 (leukocyte common antigen), CD3, CD30, and TIA-1 (cytotoxic granule marker) and Ki-67. [2468] It is important to highlight that CD30 positivity may vary, and it is more frequently expressed in large T-cell lymphomas, rather than small-to-medium-sized lesions. [5] Serum anti-gliadin antibodies are normally positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation